The religion clauses the case for separating church and state - Chemerinsky, Erwin; Gillman, Howard (Inalienable Rights Series, 2020)
The relationship between the government and religion is deeply divisive. With the recent changes in the composition of the Supreme Court, the First Amendment law concerning religion is likely to change dramatically in the years ahead. The Court can be expected to reject the idea of a wall separating church and state and permit much more religious involvement in government and government support for religion. The Court is also likely to expand the rights of religious people to ignore legal obligations that others have to follow, such laws that require the provision of health care benefits to employees and prohibit businesses from discriminating against people because of their sexual orientation. This book argues for the opposite and the need for separating church and state. After carefully explaining all the major approaches to the meaning of the Constitution's religion clauses, the book argues that the best approaches are for the government to be strictly secular and for there to be no special exemptions for religious people from neutral and general laws that others must obey. The book argues that this separationist approach is most consistent with the concerns of the founders who drafted the Constitution and with the needs of a religiously pluralistic society in the 21st century"--